The Greening of Work: How Green Is Green Enough? - Räikkönen, Timo (Nordic Journal of Working Life Studies, 2011)
Today's constantly deepening environmental problems have brought about the need to remold current work cultures along the lines of green thinking. However, profound differences still prevail between the different strands of green thought and practice with regard to the greening of work. The main purpose of this paper is to look in more detail at the arguments and implications of two differing positions, namely `environmentalism´ and `ecologism´. The ideas of corporate social responsibility, green jobs, and downshifting are chosen as objects for closer scrutiny. A critical examination of these contemporary discourses leads to the conclusion that at least so far, they all remain within the confines of environmentalism: no radical changes are presupposed in the current ways of working or in our relationship with the non-human world. Viewed from the perspective of ecologism, the studied greening efforts remain too reformist and anthropocentric to be capable of making work truly `green´.